THE DISTRIBUTION LOGISTICS PROCESS AND CUSTOMER SATISFACTION - Batista, Bianca de Lima; Casagrande, Diego José (Revista Interface Tecnológica, 2023)
Logistics is placing the right product, in the right amount, in the right place, at the right time, moving quickly and adding value to the product. The purpose of this article is to seek to understand how the distribution logistics process works, and what they do to ensure that the product is delivered with great efficiency. The research method used in this research was the Case Study together with the Bibliographic Research. The Case Study of this research was based on data researched about the company Amazon. At the end of the research we concluded that every company that has an e-commerce its differential is precisely the delivery. Delivery on time, delivery with short deadlines and what satisfies the customer and makes him always buy from the company and become loyal. Amazon does this masterfully and ends up being an example for other companies in terms of how their distribution logistics work.
Keywords: Logistics; Distribution; Amazon